2013
DOI: 10.1161/circresaha.113.301325
|View full text |Cite
|
Sign up to set email alerts
|

C2238 Atrial Natriuretic Peptide Molecular Variant Is Associated With Endothelial Damage and Dysfunction Through Natriuretic Peptide Receptor C Signaling

Abstract: A trial natriuretic peptide (ANP), a cardiovascular hormone with natriuretic, diuretic, and vasodilator activity, 1 contributes to the risk of cardiovascular events depending on either abnormal circulating concentrations or peptide structural alterations.2 In the latter regard, the molecular variant of the prepro-ANP gene characterized by the substitution of thymidine with cytosine in position 2238 affects the incidence of cardiovascular events in different human populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 27 publications
5
51
1
Order By: Relevance
“…Since previous work has demonstrated that NPR-B KO animals are normotensive (28), these observations as a whole provide convincing evidence that, physiologically, NPR-C is the primary receptor triggered by CNP to maintain vascular function and blood pressure. The thesis is supported by the acute vasodilator (29,30) and hypotensive (31)(32)(33)(34) responses to exogenous CNP and the emerging signaling role of G i -coupled NPR-C in various cell types (35)(36)(37)(38)(39). CNP also produced a concentration-dependent relaxation of human vessels that was abolished in the presence of the selective NPR-C antagonist M372049 (lead compound based on AP-811; gift of C. Veale, AstraZeneca) (25,40) and following precontraction mediated by high K + (which abrogates smooth muscle hyperpolarization; Figure 2L).…”
Section: Resultsmentioning
confidence: 99%
“…Since previous work has demonstrated that NPR-B KO animals are normotensive (28), these observations as a whole provide convincing evidence that, physiologically, NPR-C is the primary receptor triggered by CNP to maintain vascular function and blood pressure. The thesis is supported by the acute vasodilator (29,30) and hypotensive (31)(32)(33)(34) responses to exogenous CNP and the emerging signaling role of G i -coupled NPR-C in various cell types (35)(36)(37)(38)(39). CNP also produced a concentration-dependent relaxation of human vessels that was abolished in the presence of the selective NPR-C antagonist M372049 (lead compound based on AP-811; gift of C. Veale, AstraZeneca) (25,40) and following precontraction mediated by high K + (which abrogates smooth muscle hyperpolarization; Figure 2L).…”
Section: Resultsmentioning
confidence: 99%
“…NPR-C is primarily viewed as a clearance receptor that binds and internalizes NPs to remove them from the circulation [22]. However, increasing evidence suggests that NPR-C may also fulfill a variety of biological functions, potentially mediated via inhibition of adenylate cyclase and activation of phospholipase C [22][23][24]. Although the exact physiological role of the NPR-C is still to be confirmed, most of its potential biological activity is thought to stem primarily from NPR-C binding of CNP (in preference to ANP or BNP) [23].…”
Section: Natriuretic Peptide Receptorsmentioning
confidence: 99%
“…Corin is expressed primarily in the heart (3)(4)(5), where it activates atrial natriuretic peptide (ANP), 3 which promotes sodium excretion and vessel relaxation, thereby reducing blood volume and pressure (6 -10). Variants and mutations in the genes encoding corin and ANP have been found in patients with hypertension and heart disease (11)(12)(13)(14)(15)(16)(17)(18)(19), supporting the importance of the corin and ANP pathway in maintaining normal blood pressure and cardiac function. Corin and ANP may also act locally in the pregnant uterus to promote trophoblast invasion and spiral artery remodeling (20 -23), which are critical for regulating maternal blood pressure.…”
mentioning
confidence: 90%